2014
DOI: 10.12691/education-2-1-3
|View full text |Cite
|
Sign up to set email alerts
|

College Students’ Perceptions of Relations with Parents and Academic Performance

Abstract: The relationship between parent relations and college students' academic performance was examined in two studies using samples of students enrolled in two southeastern liberal arts universities (N = 466). T scores on the Relations with Parents subscale on the college version of the Behavior Assessment System for Children-2 served as the measure of student perception of parent relations and academic performance was measured using official university GPA and probation/suspension data. Results for the first study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 18 publications
(21 reference statements)
0
4
0
Order By: Relevance
“…As established by several studies, parents' educational level has a positive influence on the students' academic achievement (Gooding, 2001;Idris et al, 2020;Khan et al, 2015;Schwanz et al, 2014). Hence, parents who are welleducated or went through it all from high school to college would know and understand their children's needs and necessities, primarily when classes are held online, and it needs some stack of money to keep up.…”
Section: Resultsmentioning
confidence: 99%
“…As established by several studies, parents' educational level has a positive influence on the students' academic achievement (Gooding, 2001;Idris et al, 2020;Khan et al, 2015;Schwanz et al, 2014). Hence, parents who are welleducated or went through it all from high school to college would know and understand their children's needs and necessities, primarily when classes are held online, and it needs some stack of money to keep up.…”
Section: Resultsmentioning
confidence: 99%
“…[2][3][4][5][6][7][8][9] A great deal of research has focused on the influence of attachment and social support on the psychological well-being of adolescents and college adjustment, less attention has focused on parent relations and academic achievement for the college population and in particular, the potential joint effects of parental and peer attachment. [10] While adolescence period distinct by separation individuation, studies suggests that late adolescent college students remain strongly attached to, and influenced by, their parents. [11][12][13][14] Understanding how to promote academic achievement among adolescents has long been a challenging task for that several studies have shown that families, schools and peers are all important contextual predictors for adolescent development.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, research has indicated that the majority of young adults entering college traverse this transitional stage accompanied by their parents (Fingerman, Cheng, Tighe, Birditt, & Zarit, 2012;Gavazzi, 2012;Schwanz, Palm, Hill-Chapman, & Broughton, 2014).…”
Section: Family Relationship Between the Victim And The Offendermentioning
confidence: 99%
“…In fact, several studies have proposed that the victim's dependence on the perpetrator for support, security, and protection creates the potential to feel hurt by relational devaluation (see Lemay, et al, 2012;Shaver, Mikulincer, Lavy, & Cassidy, 2009). Moreover, if the parental involvement and support may not end when students enter college and young adulthood (Fingerman, et al, 2012;Schwanz, et al, 2014), and if dependence is a central component of feeling hurt in response to relational devaluation (Lemay, et al, 2012), the offended who highly value the family relationships and are committed to them should be more likely to feel hurt in these contexts.…”
Section: Intensity Of the Hurt Experienced By The Victimmentioning
confidence: 99%